La relación entre soporte social y salud mental durante la pandemia por COVID-19 - Florentino Santisteban, Brian Kevin (2022)
Currently, the COVID-19 pandemic has affected the mental health of the population worldwide. Therefore, the present aims to identify the methodological characteristics of the relationship between social support and mental health, analyzing the empirical evidence in research on adults during COVID-19. The design used is an applied review in psychology and electronic databases such as Scopus or Web of Science with articles published since 2020 were used. A total of 10 investigations were included that reported the association between social support and mental health in adults from four continents. All investigations used a non-probabilistic type of test for convenience, eight studies used the theoretical model of Zimet et al. (1988) for the evaluation of social support, differences were also observed in the use of instruments for the measurement of mental health and social support, they demonstrated, nine investigations reported evidence of reliability of the instruments and none of validity. Finally, the studies conclude that there is a negative relationship between social support and mental health, the first being a protective factor against depression and anxiety.